Peran Guru dalam Mengembangkan Interaksi Sosial Anak Autis di SDN Kunciran 07 - Septy Nurfadhillah; Nadia Nurrohmah; Defi Prasasti; Ulia Uswatun; Fitri Maulida; Sarah As-Sikah; Neli Agustina; Syifa Fauziah El-Abida (ANWARUL, 2021)
The purpose of this study was to obtain information about the role of classroom teachers and special assistant teachers in dealing with students with autism disorders in elementary schools. As well as to describe the characteristics of children with autism and how the active role of parents and teachers in improving communication skills and social interaction of children with autism. This study used a qualitative approach with descriptive techniques. Data was collected using observation, interview, and documentation techniques. This research uses data analysis model of Miles and Huberman, where the researcher conducts data collection, data reduction, data presentation and data verification. Checking the validity of the data using data triangulation which is done by combining and comparing data from observations with data from interviews and documentation. The data obtained were analyzed by descriptive qualitative data analysis techniques and using triangulation techniques to check the validity of the data. The results of this study indicate that there is a significant relationship between the active role of parents and school teachers in improving children's communication and social interaction skills. What is very important given to children is the acceptance of parents towards children and the social support provided by parents and teachers in the environment around children. The conclusion of this study is that children with autism require very complex treatment and require the participation and active role of parents and teachers in many matters related to the development of communication and social interaction of children.